Concurrent β-blocker Use is Associated With Improved Outcome in Esophageal Cancer Patients Who Undergo Chemoradiation: A Retrospective Matched-pair Analysis. (December 2020) - Farrugia, Mark K.; Ma, Sung Jun; Mattson, David M.; Flaherty, Leayn; Repasky, Elizabeth A.; Singh, Anurag K.
Abstract : Background: β-blocker use has been associated with improved outcomes in a number of different malignancies; however, the impact of β-blockade in esophageal cancer is not been well characterized. We compared the outcomes of esophageal cancer patients based on β-blocker usage. Methods: The charts of all 418 patients treated with radiation for esophageal cancer at our institution from April 2010 to October 2018 were analyzed. Patients who underwent treatment with palliative intent or did not finish treatment were excluded. β-blocker use was determined from the medication list at time of pretreatment consultation. Results: There were 291 esophageal cancer patients who received neoadjuvant/definitive chemoradiation therapy. The median follow-up for the cohort was 22.5 months (interquartile range: 9.6 to 41.0 mo). Within the cohort, 27.8% (n=81) of patients were taking β-blockers at the time of treatment. Those taking β-blockers had significantly improved distant control (22.2% vs. 37.9%; P =0.035). Concomitant β-blocker use was significantly associated with improved progression-free survival ( P <0.001, hazard ratio=0.42 [0.27-0.66]) and overall survival ( P =0.002, hazard ratio=0.55 [0.38-0.81]) on Cox regression analysis. Propensity score–matched pairs were created using tumor stage, nodal stage, sex, neoadjuvant versus definitive therapy, Karnofsky Performance Status, and aspirin use. This matched-pair analysis showed a significant progression-free survival ( P =0.005) benefit in esophageal cancer patients taking β-blockers. Conclusions: Concurrent β-blocker use is common within patients receiving concurrent chemoradiation for esophageal cancer. Esophageal cancer patients who received chemoradiation while taking β-blockers demonstrated significant benefits in survival-based outcomes. Abstract : Supplemental Digital Content is available in the text.